Participatory methodology for profiling the status and resilience of indigenous people's food systems in eight countries - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
The methodology was co-developed by Bioversity and FAO, along with other partners. More than 14 indigenous food systems have been profiled to date. In 2021, 8 case studies were published. FAO has also applied the methodology in China, Indonesia, and Iran with plans to expand to Ecuador, Bolivia, and Kyrgyzstan.